Looking at the relationship between job satisfaction and employee engagement - Ariana, Sunda; Helmi, Sulaiman; Natalisa, Diah; Jaya, Ade Kemala (Edelweiss Applied Science and Technology, 2024)
The study aimed to investigate the relationship between job satisfaction and employee engagement of employees. This research was quantitative using a survey method, the number of research samples was 80 people, who were selected using the cluster sampling method which is part of probability sampling. Data analysis method using Smart-PLS version 3.0 software. PLS (Partial Least Square). The research findings showed that employee engagement had a significant effect on job satisfaction, employee engagement did not have a significant effect on the non-physical work environment, employee engagement had a significant effect on competence, non-physical work environment affected job satisfaction, competence did not have a significant effect on job satisfaction, non-physical work environment mediated job satisfaction towards employee engagement, competence did not mediate job satisfaction towards employee engagement with sig, > 0.05. This research revealed that workers at PT Semen Batu raja Palembang had different levels of competence and had different employee engagement. This showed that each worker had a high creativity in completing efficient tasks and designing appropriate work methods to achieve effectiveness and efficiency. High value for work is able to increase employee satisfaction and can determine employee commitment to the organization where they work.